Complications in submental liposuction: A narrative review (Research, Society and Development, 2024)
Submental liposuction is a popular aesthetic technique for reducing fat in the submandibular area, offering facial contouring and rejuvenation. Although less invasive than facial surgeries, it poses risks such as edema, infections, and sensory alterations. Studies focused on complications in the submental region are scarce, despite anatomical features requiring precise technique and careful planning. High demand among young patients calls for strict selection criteria, informed consent, and proper postoperative protocols. Reviewing complications aims to inform professionals about risks and foster innovations to enhance safety. The aim of this study is to review and discuss the main complications associated with submental liposuction, focusing on intra- and postoperative complications and preventive measures.